Teachers’ Feedback in Group Works of EFL Learning: Does It Influence Students’ Success? - absharini kardena (English Education Department at FKIP Nommensen University, 2020)
As one of suggested teaching techniques in EFL context, one of important stages in implementing group work is allocating time for testing students’ comprehension. This stage is claimed to be an important stage since it is aimed to evaluate teaching and learning processes. Moreover, this evaluation demands any feedback in order to improve the quality of teaching and learning processes and even group work activity. In other words, group work also requires such evaluation in terms of feedbacks in order to get the maximum effect of this teaching technique for the students. However, the feedback offered cannot always affect the processes in a positive way. Thus, the teachers need to consider any guidelines in offering the feedback. This article, which is derived and further developed based on research conducted in 2013, explores the role of teachers’ feedback in relation to the success of EFL learning at MAN Solok city, a state Islamic senior high school at Solok city, West Sumatera. The research was conducted under qualitative design in which searched out how the teachers offered feedback and how it influenced students’ success in learning English as foreign language. The research found that the teachers offers two kinds of feedback; they were praise and critics.